Evaluation of the effects of silver nanoparticles on Danio rerio cornea: Morphological and ultrastructural analysis. Issue 8 (2nd May 2019) - Pecoraro, Roberta; Salvaggio, Antonio; Scalisi, Elena M.; Iaria, Carmelo; Lanteri, Giovanni; Copat, Chiara; Ferrante, Margherita; Fragalà, Giuseppe; Zimbone, Massimo; Impellizzeri, Giuliana; Brundo, Maria V.
Abstract: Although in recent years there has been intensification in the use of nanoparticles (NPs) for the production of many commercial products, few studies have been carried out to assess the risks associated with its use. Among the most used NPs, silver nanoparticles (AgNPs) have a preponderant position as they have various applications. In this study, 40 adult zebrafish were exposed to increasing concentrations of AgNPs (8, 45, and 70 μg/L) for 30 days to evaluate the effects on eyes after chronic exposure to AgNPs with an average diameter of 50 nm. From the morphological and ultrastructural analysis performed, no alteration or lesions of the corneal epithelium were detected. Abstract : Toxicity of AgNPs on the zebrafish cornea. No corneal lesions were observed after exposure of the AgNPs. Zebrafish model can be promoted for screening of the nanomaterial toxicity.